Application of Inventory Information Systems as a Work Practice Management Strategy in Improving Technology Learning in Education Management - Fika, Matias; Hutagalung, Risma (Edumaniora : Jurnal Pendidikan dan Humaniora, 2024)
This study aims to investigate the application of Inventory Information Systems (IIS) as a work practice management strategy to enhance technology learning in education management. The research explores how the integration of IIS into educational institutions' management systems can improve the efficiency and effectiveness of technology learning processes. Through a comprehensive literature review, this study examines the potential benefits of employing IIS, such as streamlining inventory management, optimizing resource allocation, and facilitating data-driven decision-making in educational settings. Additionally, the research evaluates the challenges and limitations associated with implementing IIS in education management, including infrastructure requirements, staff training needs, and data security concerns. By analyzing case studies and empirical evidence, this study seeks to provide insights into best practices for integrating IIS into education management to foster enhanced technology learning outcomes. The findings of this research contribute to the development of strategies aimed at leveraging inventory information systems as a tool for advancing technology learning in educational institutions.